Evaluation of Rocuronium Associated to Acepromazine, Propofol and Isofluorane in the Anesthesia of Female Canines Submitted to Elective Ovaryhysterectomy (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: rocuronium; female canines; ovary hysteric tomy